Optimasi Chatbot Layanan Informasi Publik Berbasis Button-Based Interaction di Kelurahan Gebang Putih Surabaya - Nailussa’ada Nailussa’ada; Hero Yudo Martono; Andhik Ampuh Yunanto; Prasetyo Wibowo; Dian Septiani Santoso; Ira Prasetyaningrum; Fitrah Maharani Humaira (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
This community service study describes the optimization of a public information service chatbot in Gebang Putih Urban Village, Surabaya. The previous Telegram-based chatbot relied on command-based interaction, requiring citizens to type specific keywords and read long messages, which likely increased interaction cost. The study aims to transform the chatbot into button-based interaction and redesign its information architecture so that services are organized hierarchically and presented in shorter steps. A descriptive qualitative research and development (R&D) approach is applied at the development and internal validation stage. Service content is aligned with the official SSWALFA portal and the Surabaya Dukcapil website, and implemented using the low-code platform ManyChat. The resulting chatbot features more structured interaction flows, with clearer service categories, requirements, and procedures. These design improvements are expected to reduce interaction cost and enhance the potential usability of the chatbot.